On-Farm Research in integrated farming systems: Addressing challenges of small farms at the field level - RAGHUVEER SINGH; N RAVISANKAR; SUNIL KUMAR (The Indian Journal of Agricultural Sciences)
The ever increasing global population has intensified the pressure on agriculture, driving a shift toward smallholder farming systems. Historically, agricultural technologies have primarily catered to large, mechanized farms, exacerbating the disparity between large and small landholders. While strides have been made in achieving food security, livelihood security for farmers remains elusive, especially for smallholders and marginal farmers, who constitute over 80% of the global farming population. In India, these farmers account for nearly one-fourth of the world's small and marginal farms, cultivating less than 2 ha of land. Raising the income of these smallholders poses a significant challenge to researchers, policymakers, and governments. Given the constancy of land resources, horizontal intensification is not possible. The solution lies in vertical intensification through diversification, exemplified by the Integrated Farming System (IFS). IFS integrates various farming enterprises, allowing the by-products of one enterprise to serve as inputs for another, enabling resource recycling, efficient use of labour and space, and reduced market dependency. However, implementing on-station IFS models directly at farmers' fields is impractical due to high initial costs. Interventions targeting critical inputs within existing farming systems, as demonstrated by the All India Coordinated Research Project on Integrated Farming Systems–On-Farm Research (AICRP-Integrated-IFS-OFR), offer a promising alternative. By investing just ₹7,889 this approach achieved an 86% increase in net income within two years of implementation (2022–24), showcasing its potential to improve the livelihoods of small and marginal farmers effectively.